ESCCA recommendations for managing measurement uncertainty in ISO 15189 accredited flow cytometry laboratories: A risk‐based approach - Ulrika Johansson; Catarina Martins; Neil McIver‐Brown; Eleni Linskens; Efthalia Yiannaki; Thomas Keller; David Bloxham; Francesco Buccisano; Kathryn Clarke; Maria João Acosta; Katy Jones; Wolfgang Kern; et al. (Cytometry Part B: Clinical Cytometry, 2026)
Abstract In ISO 15189‐accredited medical laboratories, estimation and management of measurement uncertainty (MU) is a fundamental requirement. However, both the theoretical and practical aspects of MU estimation in medical testing are still evolving. In the specific context of clinical flow cytometry, only a limited number of publications address this subject. A survey distributed to European Society of Clinical Cell Analysis members revealed that guidance in this area would be valuable, as current practices vary significantly across laboratories and countries. To address this, a dedicated working group was established to explore how MU could be implemented in flow cytometry laboratories in a manner that embeds it in the laboratory's quality system and that is consistent with ISO 15189:2022 requirements, with the view to avoid it becoming a mere compliance task. Given that a significant number of flow cytometry assays yield qualitative rather than quantitative results and considering the patient‐focused, risk‐based perspective of the 15189:2022 standards, we approached MU from the perspective of understanding process variability. This paper details and summarizes the result of our work. We present a set of recommendations aimed to help flow cytometry laboratories approach this subject effectively; providing guidance for the types of assays that may be suited for an estimated and monitored MU, and recommendations for how to adopt a structured, risk‐based methodology to minimize sources of variation for all assays. This involves identifying sources of uncertainty throughout the analytical process, evaluating their impact, and prioritizing control efforts where the risk to result integrity and patient safety is greatest.